Pengukuran Kinerja Supply Chain Management Di Toko Aki Menggunakan Metode SCOR - Andrean, Reza; Marwan, Marwan (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
A battery store is a business that specifically sells car batteries or batteries. In running this business, it is highly dependent on the smooth operation of good inventory management. A good supply of goods will be the main key in ensuring the availability of goods to meet consumer demand. Companies need to have a good supply chain management system to have quality products or services. Several aspects and stakeholders must work well to ensure that the supply chain flow runs appropriately starting from suppliers, companies, distribution, to customers. Supply Chain Operation Reference (SCOR) is a performance measurement model in the supply chain that can explain a company's supply chain in detail through measurement indicators that are appropriate to the company. To calculate the SCOR method using AHP weighting. There are 10 indicators obtained and 3 indicators need to be improved to improve the performance of Supply Chain Management at Toko Aki, namely the Planning cycle Time indicator with a value of 33.33, Timely delivery performance by suppliers with a value of 66.66 and Timely delivery performance by the company 85.5. Improvement proposals are made on indicators with a value of < 90 (Excellent).